Residual seismic load capacity of fire-damaged rubber bearings of r.c. base-isolated buildings. (September 2017) - Mazza, Fabio
Abstract: Irreversible deterioration in the base-isolation system of framed buildings exposed to high temperatures during a fire has raised concerns about the reliability of elastomeric isolators (e.g. High-Damping-Laminated-Rubber Bearings, HDLRBs, and Lead-Rubber Bearings, LRBs) during seismic aftershocks. The main objective of this research is to evaluate mechanical property loss of HDLRBs and LRBs, based on prediction of their temperature profile. To this aim, transient analysis corresponding to the Eurocode 1 time-temperature fire curves, carried out by means of three-dimensional finite element modelling of HDLRBs and LRBs, is compared with steady response, defined as a heat conduction problem of a constant flux in an infinite circular cylinder. A 200 °C isotherm method is used to evaluate reduction of the mechanical properties of the fire-damaged isolators. To verify the damage in the nonlinear seismic response following fire, a numerical investigation is carried out on six-storey reinforced concrete (r.c.) base-isolated framed buildings comprising a basement and five storeys above ground. Three scenarios are considered, with the fire compartment confined to the area of the base-isolated level (i.e. F0), first level of the superstructure (i.e. F1) and both levels (i.e. F0/1). Base-isolated structures in a no fire situation are compared with those in the event of fire at different durations of resistance. A multi-record nonlinear incremental dynamic analysis of the test structures considers two sets of seven near- and far-fault earthquakes, respectively. Fire loading before earthquake confirms significant reduction of the mechanical and geometrical properties of the HDLRBs and LRBs inducing amplification in the structural response of base-isolated structures. Highlights: Three-dimensional finite element thermal analysis of High-Damping-Laminated-Rubber Bearings (HDLRBs) Three-dimensional finite element thermal analysis of Lead-Rubber Bearings (LRBs) Residual seismic load capacity of r.c. base-isolated buildings with fire-damaged HDLRBs and LRBs Multi-record nonlinear incremental dynamic analysis of r.c. base-isolated buildings